Tutorías académicas y su incidencia en el mejoramiento del aprendizaje de los y las estudiantes de educación básica de la unidad educativa Caluma del cantón Caluma, provincia Bolívar - Sánchez Bonilla, Gredy Irlanda (2017)
The research, whose result supports the writing of this thesis, aimed to identify the incidence of academic tutoring, in the improvement of the learning of students of Basic Education of the Caluma Educational Unit, For its development methods were used at the theoretical and empirical level of scientific research, as well as mathematical and statistical methods. The programmed research activity was developed in two phases. The first was to diagnose the existing conditions in the institution to face the academic tutoring, as well as the preparation of the teachers to develop it. In the second in addition to developing the methodological strategy, it was submitted to the theoretical assessment by seven experts duly selected. The research reached conclusions of high scientific and methodological value that if taken into account by the pertinent authorities could considerably improve the conditions in the institution for the development of academic tutoring, among the conclusions highlights the following. The preparation in specific conditions of the teacher whose content is how to plan, organize and control the academic tutoring considerably improves the pedagogical direction of the planned teaching-learning process